Preprocessing and Hybrid Biochemical/Thermochemical Conversion of Short Rotation Woody Coppice for Biofuels - Williams, C. Luke; Emerson, Rachel M.; Hernandez, Sergio; Klinger, Jordan L.; Fillerup, Eric P.; Thomas, Brad J. (Frontiers in Energy Research, 2018)
Preprocessing with air classification, followed by a hybrid biochemical/thermochemical conversion scheme, was utilized to improve the quality of short rotation woody coppice (SRWC) for biofuels production. Air classification improved sugar release during enzymatic hydrolysis by 6–12% for poplar and willow coppice respectively. Total theoretical sugar release for these hardwood coppices was 70%, which suggests that they could be utilized for biochemical conversion. Improved sugar yields after air classification were tied to compositional changes of reduced ash and extractives which can neutralize dilute acid pretreatment and inhibit fermentation. However, air classification was shown to have little to no effect on pyrolytic thermochemical conversion as it removed material without returning a significant improvement in liquid yield. It was also shown that pyrolysis of biochemical conversion lignin rich residue gives liquid yields comparable to whole tree (without any fractionation) pyrolysis, with a higher quality oil that has 60% reduced total acid number. Using this combined biochemical/thermochemical conversion strategy can improve yields of fermentable sugars and pyrolysis liquid above 80%, instead of the 60% yield of sugars or bio-oil when using a single conversion strategy. Overall, it has been shown that preprocessing and hybrid conversion pathways are a viable strategy for maximizing biorefinery viability.